Living by the sea: place attachment, coastal risk perception, and eco-anxiety when coping with climate change - Parreira, Natacha; Mouro, Carla (Frontiers in Psychology, 2023)
Climate change poses major threats to coastal regions. In Portugal, the Aveiro district is one of the most vulnerable areas due to urbanized areas’ exposure to the dangers of rising water. The prospect of flood threats can trigger a range of cognitions and emotions that affect adaptation and mitigation measures’ success. This study sought to examine whether active and traditional place attachment is associated with residents’ active and passive coping strategies to deal with the risk of rising water levels. An additional aim was to clarify whether these relationships are mediated by risk perception and eco-anxiety. The links between individuals’ level of trust in authorities and coping mechanisms were also examined. An online questionnaire was completed by 197 Aveiro residents. The data show that active place attachment is connected to greater risk perception, eco-anxiety, and adoption of active coping strategies (e.g., problem solving). Low eco-anxiety was also found to have a positive effect on active coping strategies. Lower trust in the responsible authorities was additionally associated with active coping mechanisms. Overall, the results support the sequential mediation model for active coping but not for passive coping. The findings reinforce the need to consider cognitive factors (e.g., risk perception) and emotional factors (e.g., place attachment and practical eco-anxiety) to understand more fully how coastal residents deal with flood threats. Practical implications for policymakers are discussed.